British Medical Journal. Supplement : A general medical service for the nation ([London : British Medical Association])
1938-04-30 1938 1930s 14 pages JT CTEE 3/2 1937-8 A.R.M. 2a 1938 SUPPLEMENT TO THE BRITISH MEDICAL JOURNAL LONDON SATURDAY APRIL 30 1938 A GENERAL MEDICAL SERVICE FOR THE NATION CONTENTS Para. INTRODUCTION AND SUMMARY 1-19 I.— THE PROBLEM 20-23 II.— GENERAL PRINCIPLES 24-41 III.— THE PLAN 42-63 (a) General Practitioner Services 43-51 (B) Other Non-Institutional Services 52-59 (c) Institutional Services 60-63 IV.— SOME SPECIAL PROBLEMS 64-108 (a) A National Maternity Service 64-74 (b) Hospital Problems 75-94 (c) Domiciliary Public Assistance Medical Service 95-97 (d) Existing Public Health Services 98-102 (e) Some Special Services.................. 103-108 V.— ADMINISTRATION ........................ 109-122 INTRODUCTION AND SUMMARY 1. In discussions on proposals for a general medical service for the nation the major details, and suggestions as to how they should be carried out, are of the first importance. Many such details and suggestions are included in subsequent sections of this report. It is necessary, however, to clarify them by a more general and succinct survey in order that each may fall into its proper place. 2. The field is not clear, to start with. If it were it might not be very difficult to construct, at any rate on paper, a health scheme which would be symmetrical, logical, complete, and effective both clinically and administratively. We find, however, the ground occupied — but by no means covered — with a number, even a plethora, of health services better, on the whole, than those existing in any other country. Nevertheless these services, each good in itself, have grown up or been established in a piecemeal, independent, more or less haphazard fashion, and in consequence there is much overlapping and unnecessary complication and confusion, while there are yet large gaps in the provision needed in a reasonably complete service. Moreover, existing areas of health administration are often unsuitable, but any proposals for reform must take into consideration the historical and practical circumstances which have brought them into being. 3. In formulating, then, a scheme for a general medical and health service for the nation it is not attempted to set out one which is ideal in the abstract or even perfectly logical, either in its administrative or in its clinical aspect. We seek, rather, while recognizing existing conditions and circumstances, so to adjust, modify, and extend present services and administrative arrangements as to produce a co-ordinated and, as far as possible, unified system, effective and reasonably complete. 4. In England and Wales the only existing agency which can act as a unifying force is the Ministry of Health.* As such a force, however, it is both ineffective and incomplete. Its several departments appear to function to a great extent independently of one another. It has farmed out the control of the school medical service to the Board of Education in spite of the intentions of Parliament. The control of other important health services remains with the Home Office. It would be an advantage if, for the purposes of central administration and supervision, these divisions and imperfections could be abolished. 5. Locally there are now two systems of medical provision, one under the auspices of the Insurance Committees of counties and county boroughs, another under the auspices of local authorities, either counties or county boroughs or smaller (but often very populous) county districts. These systems are independent of one another, * In Scotland the appropriate agency is the Department of Health. 1744 292/847/1/60